Preoperative Neutrophil-to-Lymphocyte Ratio as a New Prognostic Marker in Hepatocellular Carcinoma after Curative Resection() - Liao, Weijia (Neoplasia Press, 2014)
BACKGROUND: Preoperative peripheral blood neutrophil-to-lymphocyte ratio (NLR) has been proposed to predict prognosis of hepatocellular carcinoma (HCC). However, the cutoff value of NLR in several studies is not consistent. This study aims to investigate the correlation of preoperative NLR with clinicopathologic features and the prognosis in patients who have undergone resection for HCC. METHODS: Clinical data of 256 patients with HCC who underwent radical hepatectomy were retrospectively analyzed. The patients were divided into the low-NLR group (NLR ≤ 2.31) and the high-NLR group (NLR > 2.31). A univariate analysis was performed to assess clinicopathologic characteristics that influenced disease-free survival (DFS) and overall survival (OS) in patients. The significant variables were further analyzed by a multivariate analysis using Cox regression. The Kaplan-Meier method was used to assess the DFS and OS rate. RESULTS: The value of NLR was associated with tumor size, clinical tumor-node-metastasis (TNM) stage, portal vein tumor thrombus (PVTT), distant metastasis, and aspartate aminotransferase (AST) in HCC. NLR > 2.31, size of tumor > 5 cm, number of multiple tumors, III-IV of TNM stage, PVTT, distant metastasis, and AST > 40 U/l were predictors of poorer DFS and OS. NLR > 2.31, size of tumor > 5 cm, III-IV of TNM stage, and AST > 40 U/l were independent predictors of DFS and OS. CONCLUSION: Preoperative NLR > 2.31 was an adverse predictor of DFS and OS in HCC after hepatectomy. This study suggested that NLR might be a novel prognostic biomarker in HCC after curative resection.